A highly sensitive fluorescent sensor based on small molecules doped in electrospun nanofibers: detection of explosives as well as color modulation1. Issue 31 (21st August 2015) - Xue, Wei; Zhang, Yang; Duan, Juanjuan; Liu, Dong; Ma, Yawei; Shi, Naien; Chen, Shufen; Xie, Linghai; Qian, Yan; Huang, Wei
<x xml:space="preserve">Abstract</x> A new type of highly sensitive low-cost sensor towards nitro-compounds based on PEO/MePyCz composite nanofibers is reported. The composite nanomaterials may also be applied in nano-optoelectronics devices, light-emitting diodes or biological sensors.